2022
DOI: 10.13057/nusbiosci/n140107
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of arbuscular mycorrhizal fungi and root colonization in Polygonatum verticillatum

Abstract: Abstract. Kumar A, Tapwal A. 2022. Diversity of arbuscular mycorrhizal fungi and root colonization in Polygonatum verticillatum. Nusantara Bioscience 14: 53-63. Diversity of arbuscular mycorrhizal fungi (AMF) associated with Polygonatum verticillatum (L.) All. was investigated in two sites of Himachal Himalaya, India. A total of 15 AMF species were isolated and identified from the rhizosphere soil of P. verticillatum. The spore density was 1.48 ± 1.91 and 3.99 ± 3.78 per 20 gram of rhizosphere soil at site-I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…It has been reported that low pH (5.5-6.5) favors the production of more spores by Glomus species (Wang et al 1993). Moreover, several studies worldwide reported Glomerales members' predominance in medicinal plants' rhizosphere (Thapa et al 2015;Wang and Jiang 2015;Verma et al 2019;Kumar and Tapwal 2022). The species were found more evenly distributed in the winter season at both the sites of A. glauca.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been reported that low pH (5.5-6.5) favors the production of more spores by Glomus species (Wang et al 1993). Moreover, several studies worldwide reported Glomerales members' predominance in medicinal plants' rhizosphere (Thapa et al 2015;Wang and Jiang 2015;Verma et al 2019;Kumar and Tapwal 2022). The species were found more evenly distributed in the winter season at both the sites of A. glauca.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, before the cultivation of medicinal plants through the artificial inoculation of AMF, assessing the dominant mycorrhizal mycobiota in the selected medicinal plant's rhizosphere region is preferable. Many researchers have observed the diversity of AMF in the rhizospheres of medicinal and aromatic plants (Koul et al 2012;Zeng et al 2013;Song et al 2019;Kumar and Tapwal 2022). The AMF association has been reported with most medicinal and aromatic plants, and it was observed that host and climatic conditions greatly influenced their diversity.…”
Section: Introductionmentioning
confidence: 99%